Social media policies in the Department of Defense—Do they address the risk?. Issue 2 (2nd April 2016) - Cole-Miller, Katherine "Suzy"; Ward, William "Doug"; Fruhling, Ann; Cooper, Kathryn Dempsey
ABSTRACT: The rapid adoption and increased availability of social media has brought dynamic changes to the way people and organizations access and distribute information. Use of social media carries an inherent risk. Organizations use policies to encourage acceptable and responsible use of social media while limiting the activities they perceive as causing the most risk. This article will explore the social media policies of the Department of Defense by using a previously established methodology to determine if the policies are sufficiently addressing the risk as well as encouraging responsible use. The aim of this study is to provide recommendations based on the analysis and review of the policies.